Semi-Individualized Acupuncture for Insomnia Disorder and Oxidative Stress: A Randomized, Double-Blind, Sham-Controlled Trial - Yeung WF (Dove Medical Press, 2021)
Wing-Fai Yeung,1 Branda Yee-Man Yu,2 John Wai-Man Yuen,1 Janice Yuen Shan Ho,1 Ka-Fai Chung,3 Zhang-Jin Zhang,4 Deejay Suen Yui Mak,5 Lorna Kwai-Ping Suen,6 Lai-Ming Ho7 1School of Nursing, The Hong Kong Polytechnic University, The Hong Kong SAR, People’s Republic of China; 2Department of Psychology, The University of Hong Kong, The Hong Kong SAR, People’s Republic of China; 3Department of Psychiatry, The University of Hong Kong, The Hong Kong SAR, People’s Republic of China; 4School of Chinese Medicine, The University of Hong Kong, The Hong Kong SAR, People’s Republic of China; 5School of Medical and Health Sciences, Tung Wah College, The Hong Kong SAR, People’s Republic of China; 6School of Nursing, Tung Wah College, The Hong Kong SAR, People’s Republic of China; 7School of Public Health, The University of Hong Kong, The Hong Kong SAR, People’s Republic of ChinaCorrespondence: Wing-Fai YeungSchool of Nursing, The Hong Kong Polytechnic University, Room FG429, Hung Hom, Hong Kong, People’s Republic of ChinaEmail jerry-wf.yeung@polyu.edu.hkBackground: Acupuncture is an alternative treatment for improving sleep, and it may attenuate oxidative stress, which is a possible pathophysiological factor in insomnia. The aim of this study was to examine the efficacy and safety of a semi-individualized acupuncture in improving sleep and explore its effect on oxidative stress parameters in adults with insomnia disorder.Methods: In this randomized sham-controlled trial, 140 participants were randomly assigned to either a 4-week semi-individualized traditional acupuncture (TA) or noninvasive sham acupuncture (SA). The primary outcome measure was the sleep-diary-derived sleep efficiency. Other outcomes included sleep diary and actigraphy, Insomnia Severity Index, anxiety and depressive symptoms, and quality of life. Blood samples were taken to measure oxidative stress parameters (malondialdehyde, glutathione peroxidase, paraoxonase, and arylesterase).Results: Although no significant difference was found in the primary outcome measure, both sleep-diary-derived and actigraphy-derived total sleep time (TST) were significantly increased in the TA group at 1-week posttreatment (mean difference in sleep diary = 22.0 min, p = 0.01, actigraphy = 18.8 min, p = 0.02). At 5-week posttreatment follow-up, a significantly higher proportion of participants in the TA group showed sleep-diary-derived sleep efficiency (SE) ≥ 85% than in the SA group (55.6% versus 36.4%, p = 0.03).Conclusion: TA and SA did not significantly differ in improving subjective sleep efficiency in individuals with insomnia disorder. However, the TA group showed a short-term effect on improving TST as measured by both sleep diary and actigraphy at 1-week posttreatment, but there were no differences in the oxidative stress parameters.Clinical Trial Registration: Registry: ClinicalTrials.gov; Title: Acupuncture in the Modulation of Peripheral Oxidative Stress Insomnia; Identifier NCT03447587; URL: https://clinicaltrials.gov/ct2/show/NCT03447587.Keywords: sleep, electroacupuncture, oxidative stress, placebo, Chinese medicine, acupoints